Perception of medical students’ about problem-based learning at Jouf University - Altaf Bandy (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate students’ perceptions of problem-based learning tutorial sessions. Methods: This cross-sectional study, conducted from March 2019 to May 2019, surveyed clinical phase students at Jouf Universities’ College of Medicine. After obtaining ethical approval and informed consent, an electronic questionnaire was used to collect students’ perceptions of PBL sessions, tutors’ session facilitation, and tutors’ student evaluation fairness. A five-point Likert scale was used for data collection, presenting agree, disagree, and neutral response percentages. Results: With a viewership rate of 89.3% (59/66), 56 students consented to participate (participation rate of 84.8%). However, only 51 (77.27%) students completed the electronic questionnaire: 23 (45%) males and 28 (55%) females. The agreement mean perception score was 4.73± 2.13 regarding various statements characterizing PBL sessions. The majority (72.5%) of student’s perceived PBL sessions as interactive. However, 66.7% noticed content repetition within PBL, and lectures. In general, lesser mean score of agreement of 1.33±1.07 was observed on tutors’ facilitation of PBL sessions and their students’ evaluations. Conclusion: Students’ perceived PBL as effective interaction sessions, but did not positively perceive tutors’ evaluations of sessions and this remains a concern. The study offers potential solutions to avoid dysfunctional hybrid PBL educational strategy including limiting the number and content of the lectures, effective academic advising and systematic evaluation of PBL gained skills to ensure the desired competencies persist. Keywords: Problem-based learning; Interactive sessions; Collaborative learning, Tutor feedback; Self-directed learning Continuous...